NGAJI ASIK SAMBIL NGOPI: STRATEGI BRANDING KOMUNITAS “TERAS DAKWAH” DI YOGYAKARTA, INDONESIA (LEARNING ISLAM WHILE ENJOYING COFFEE: A BRANDING STRATEGY OF “TERAS DAKWAH" COMMUNITY IN YOGYAKARTA, INDONESIA) - Eko Saputra (Jurnal Sosiologi Reflektif, 2022)
The hybridity of Muslim youth with popular culture has had an influence on the da'wah packaging strategy carried out by many da'wah communities in Indonesia, including the Teras Da'wah Community in Yogyakarta, Indonesia. The packaging of da'wah with a more popular, fun, and modern cover has made Teras Da'wah as one of da'wah communities with the most wanted by many younger Muslims in Indonesia. This article aims to describe how the branding strategy is run by the Teras Da'wah Community using a qualitative research approach, namely through ethnographic and netnographic studies for six (6) months in the Teras Da'wah Community. The results of the study reveal that the appreciation of popular culture among young people today has a significant role in 'attracting' these millennials to recite the Koran in a relaxed but serious manner at Teras Da'wah. The form of this appreciation is packaged from the selection of an attractive logo, the interior of the room that resembles a cafe, the study content packaged in slang and the clustering of the study program according to the level of understanding of the members. The consequence of this strategy is the increasingly hybrid identity of Muslim youth in Indonesia due to the intersection between Islamic values and popular culture that has long been attached to them.Hibriditas anak-anak muda muslim dengan budaya populer telah membawa pengaruh pada strategi pengemasan dakwah yang dilakukan oleh banyak komunitas dakwah di Indonesia. Salah satu diantaranya yang telah menerapkan strategi tersebut adalah Komunitas Teras Dakwah di Yogyakarta, Indonesia. Pengemasan dakwah dengan cover yang lebih ngepop, fun, dan modern telah menjadikan Teras Dakwah sebagai komunitas dakwah yang diminati oleh banyak anak-anak muda muslim di Indonesia. Artikel ini bertujuan untuk mendeskripsikan bagaimana strategi branding yang dilakukan oleh Komunitas Teras Dakwah dengan menggunakan pendekatan penelitian kualitatif, yakni melalui studi etnografi dan netnografi selama enam (6) bulan di Komunitas Teras Dakwah. Hasil penelitian mengungkapkan bahwa apresiasi Teras Dakwah terhadap budaya populer di kalangan anak muda saat ini memiliki peran signifikan dalam ‘menarik’ milenial ini untuk mengaji dengan santai tapi serius di Teras Dakwah. Wujud apresiasi ini dikemas dari pemilihan logo yang menarik, interior ruangan yang menyerupai kafe, konten kajian yang dikemas dengan bahasa gaul dan klusterisasi program kajian sesuai dengan tingkat pemahaman anggota. Konsekuensi dari strategi ini adalah semakin hibridnya identitas anak-anak muslim di Indonesia akibat persinggungan antara nilai-nilai Islam dengan budaya populer yang sudah lama melekat pada diri mereka.